2019
DOI: 10.1016/j.jorganchem.2018.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Chalcogenide-capped triiron clusters [Fe3(CO)9(μ3-E)2], [Fe3(CO)7(μ3-CO)(μ3-E)(μ-dppm)] and [Fe3(CO)7(μ3-E)2(μ-dppm)] (E = S, Se) as proton-reduction catalysts

Abstract: Chalcogenide-capped triiron clusters [Fe3(CO)9(3-E)2], [Fe3(CO)7(3-CO)(3-E)(-dppm)] and [Fe3(CO)7(3-E)2(dppm)] (E = S, Se) as proton-reduction catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 75 publications
(52 reference statements)
1
10
1
Order By: Relevance
“…These include the disulfide-capped cluster [Fe 3 (CO) 9 (μ 3 -S) 2 ] 27,28 together with various diphosphine derivatives. 29 We and others 32 have investigated the proton-reduction chemistry of a series of sulfur and selenium-containing mono-and dichalcogenide-capped clusters [Fe 3 (CO) 7 (μ 3 -CO)(μ 3 -E)(μ-dppm)] and [Fe 3 (CO) 7 (μ 3 -E) 2 (μ-dppm)] (E = S, Se). While these clusters can act as proton-reduction catalysts, their activity is limited by the instability of the anions generated upon reduction, possibly due to carbonyl loss, and the relatively high potentials required for efficient proton reduction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include the disulfide-capped cluster [Fe 3 (CO) 9 (μ 3 -S) 2 ] 27,28 together with various diphosphine derivatives. 29 We and others 32 have investigated the proton-reduction chemistry of a series of sulfur and selenium-containing mono-and dichalcogenide-capped clusters [Fe 3 (CO) 7 (μ 3 -CO)(μ 3 -E)(μ-dppm)] and [Fe 3 (CO) 7 (μ 3 -E) 2 (μ-dppm)] (E = S, Se). While these clusters can act as proton-reduction catalysts, their activity is limited by the instability of the anions generated upon reduction, possibly due to carbonyl loss, and the relatively high potentials required for efficient proton reduction.…”
Section: Introductionmentioning
confidence: 99%
“…Herein we report the electrochemical and electrocatalytic reduction of protons to hydrogen by a series of 50-electron telluride-capped clusters, and a comparison of their behaviour with that of related sulfur-and selenium-capped derivatives. [27][28][29][30][31][32]…”
Section: Introductionmentioning
confidence: 99%
“…Recently, other mononuclear iron catalysts have been developed by several groups, [7][8][9][10][11][12][13][14][15] some of which are able to catalyse proton reduction more efficiently than the majority of diiron biomimics [15]. Low-valent iron clusters have attracted attention as potential electrocatalysts due to the delocalized nature of bonding in the cluster core that can lead to low reduction potentials and stable reduced species [16][17][18][19][20][21][22][23][24][25][26][27]. Thus we and others have reported electrocatalytic proton reduction by the tetrairon nitrido-, carbido-and oxo-clusters [NEt 4 ][Fe 4 (CO) 12 (μ 4 -N)] [16,17], [NEt 4 ] 2 [Fe 4 (CO) 12 (μ 4 -C)] [17] and [Fe 4 (CO) 10 (κ 2 -dppn)(μ 4 -O)] [18], respectively, which show moderate catalytic activity in organic solvents with their sodium salts also being able to operate in water [17].…”
Section: Introductionmentioning
confidence: 99%
“…The diphosphine derivative [Fe 3 (CO) 5 (κ 2 -dppv) 2 (μ 3 -S) 2 ], with a more electron-rich cluster core, is protonated by strong acids such as HBF 4 •Et 2 O and displays catalysis initiated by protonation [21]. Recently, we have also investigated the selenide-and telluride-derivatives of [Fe 3 (CO) 9 (μ 3 -S) 2 ] (Chart 1) and found that the nature of the chalcogenide exerts a significant influence on their redox response and electrochemical properties [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation